A green route for the cross-coupling of azide anions with aryl halides under both base and ligand-free conditions: exceptional performance of a Cu2O–CuO–Cu–C nanocomposite. Issue 45 (18th July 2018) - Karimzadeh, Morteza; Niknam, Khodabakhsh; Manouchehri, Neda; Tarokh, Dariush
Abstract : Ligand-free and base-free conditions were used for the preparation of aryl azides using the cross-coupling of sodium azide and aryl halides catalysed by Cu2 O–CuO–Cu–C. Abstract : A convenient, inexpensive and effective route for the preparation of a Cu2 O–CuO–Cu–C nanocomposite is described here by applying Cu(ii ) as a source of copper. Characterization of the nanocomposite was performed with X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), high-resolution TEM (HR-TEM), field emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy (XPS), and energy-dispersive X-ray spectroscopy (EDX). Analysis of the data showed that the particles of the nanocomposite are uniformly distributed and show high catalytic activity in the cross-coupling of sodium azide with various aryl iodides and bromides. This nanocomposite has a high level of performance, and even led to the synthesis of the products at room temperature. In addition, this is the first report of the synthesis of aryl azides under both base- and ligand-free conditions. For the first time, both ligand- and base-free conditions were applied for the synthesis of aryl azides, which implies exceptional performance of the Cu2 O–CuO–Cu–C nanocomposite. Simultaneous removal of the base and ligand in a green solvent is the main advantage of this reaction. Unfortunately, aryl bromides and aryl iodides with electron-withdrawing functional groups in their scaffold did not give the desired aryl azides.